Fabrication and mechanical properties of h-BN based composites containing dual glass phases. Issue 9 (August 2018) - Chen, Juanjuan; Chen, Jixin; Zhang, Xi; Hu, Minmin; Li, Meishuan
Abstract: In this work, h -BN based composites containing amorphous silica and ytterbium silicate glass phases were successfully fabricated by in situ hot pressing process. The powder mixtures of h -BN, Yb2 O3, SiO2 and sintering additive (Al2 O3 ) were hot pressed at 1880 °C for 1 h under 30 MPa in Ar atmosphere. In the composites, β-Yb2 Si2 O7 phase produced from the reaction between Yb2 O3 and SiO2 disappears completely and transforms to Yb-Si-Al-O glass when the amount of Al2 O3 is ≥1.5 wt.%. The Vickers hardness, flexural strength, and compressive strength reached the maximum values of 2.38 ± 0.08 GPa, 337 ± 22 MPa and 950 ± 34 MPa, respectively, as 1.5 wt.% Al2 O3 was added. The strengthening effects were attributed to the fine spherical microstructure of Yb-Si-Al-O glass particles, strong [AlO4 ] coordination state, and residual compressive stress in glass phases.